2020
DOI: 10.1021/acs.inorgchem.0c01173
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral Molybdenum Cluster Complexes with Optimized Properties for Photodynamic Applications

Abstract: Two new octahedral molybdenum cluster complexes act as an efficient singlet oxygen supplier in the context of the photodynamic therapy of cancer cells under blue-light irradiation. These complexes integrate the {Mo6I8}4+ core with 4′-carboxybenzo-15-crown-5 or cholate apical ligands and were characterized by 1H NMR, HR ESI-MS, and CHN elemental analysis. Both complexes display high quantum yields of luminescence and singlet oxygen formation in aqueous media associated with a suitable stability against hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 30 publications
(84 reference statements)
4
34
0
Order By: Relevance
“…The results showed that non-activated TMB, CMB and CMIF loaded nanoparticles were not toxic up to 15 µM (figure 4). These results were in adequation with the toxicity of the previously reported Mo 6 complexes (Kirakci et al, 2020). The cellular viability obtained for all nonactivated CNPs decreased with increasing cluster concentrations (for example, with CMIF loaded nanoparticles with a P/C ratio of 2.5, the cellular viability decreased from 98% to 2% when concentration was increaded from 0.5 to 50 µM).…”
Section: Cellular Uptake and In Vitro Cytotoxicitysupporting
confidence: 86%
“…The results showed that non-activated TMB, CMB and CMIF loaded nanoparticles were not toxic up to 15 µM (figure 4). These results were in adequation with the toxicity of the previously reported Mo 6 complexes (Kirakci et al, 2020). The cellular viability obtained for all nonactivated CNPs decreased with increasing cluster concentrations (for example, with CMIF loaded nanoparticles with a P/C ratio of 2.5, the cellular viability decreased from 98% to 2% when concentration was increaded from 0.5 to 50 µM).…”
Section: Cellular Uptake and In Vitro Cytotoxicitysupporting
confidence: 86%
“…Thus, 1NPs displayed phototoxicity which is among the highest ever reported for Mo 6 -based photosensitizing systems in the presence of foetal bovine serum (FBS), comparable to the phototoxicity of [Mo 6 I 8 L 6 ] 2− cluster complexes bearing crown-ether carboxylate or cholate apical ligands (1.4 and 1.5 μM, respectively). 14 Only a mitochondrion-targeting Mo 6 complex with a net positive charge displayed higher phototoxicity with an IC 50 of 100 nM, but in this case, high phototoxicity was associated with substantial dark toxicity characterized by an IC 50 of 5 μM. 13 Here, the therapeutic window of 1NPs is wider with more than 200 times higher phototoxicity over dark toxicity.…”
Section: Resultsmentioning
confidence: 93%
“…4A and B), resembling the previously described uptake of Mo 6 cluster complexes. 11,14 Spinning disc confocal microscopy showed binding of 1NPs to cultured cells with a portion of the material localized in cell vesicles (Fig. 4C).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] To date, a variety of materials (liposomes, polymers, gold, Fe 3 O 4 , mesoporous silica, upconversion nanoparticles, and metal-organic frameworks) [11][12][13][14][15] have been developed to construct nanocarriers for delivering various therapeutic agents like antitumor drugs, inhibitors, proteins, nucleic acids, and even probes in tumor therapy. [16][17][18] Among them, mesoporous silica nanoparticles (MSNs) have achieved increasing attention in biomedicine for tumor therapy due to their biocompatibility, mesoporous structure with large specific surface area and pore volume, and easy surface functionalization, which facilitate to deliver guest cargos. 19,20 For example, Rao et al proposed to construct a MSNs-based nanoplatform as a reactive oxygen species (ROS)-responsive magnetic resonance (MR) imaging-guided photodynamic chemotherapeutic agent (DOX-R-MSN).…”
Section: Introductionmentioning
confidence: 99%